Real-Time Visual Effects for Game Programming - Kim, C.-H (Springer, 2015)
This book introduces the latest visual effects (VFX) techniques that can be applied to game programming. The usefulness of the physicality-based VFX techniques, such as water, fire, smoke, and wind, has been proven through active involvement and utilization in movies and images. However, they have yet to be extensively applied in the game industry, due to the high technical barriers. Readers of this book can learn not only the theories about the latest VFX techniques, but also the methodology of game programming, step by step. The practical VFX processing techniques introduced in this book will provide very helpful information to game programmers. Due to the lack of instructional books about VFX-related game programming, the demand for knowledge regarding these high-tech VFXs might be very high.